Cu(OAc)2/TEMPO Cooperative Promoted Hydroamination Cyclization and Oxidative Dehydrogenation Cascade Reaction of Homopropargylic Amines. Issue 1 (27th November 2017) - Kong, Yuanfang; Wumaier, Kediliya; Liu, Yingze; Jiang, Chunhui; Wang, Shuai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: A novel and efficient Cu(OAc)2 ‐catalyzed hydroamination cyclization and 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO)‐mediated oxidative dehydrogenation cascade reaction of homopropargylic amines has been developed. A library of 1, 2‐disubstituted pyrrole derivatives were obtained in good‐to‐high yields in one pot with no step‐by‐step feeding process. This reaction involved TEMPO playing dual roles as both an oxidative dehydrogenation reagent and a ligand. An insight into the reaction mechanism was obtained by using several analytical determination methods. Abstract : Let′s cooperate : A novel and efficient Cu(OAc)2 ‐catalyzed hydroamination cyclization and 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO)‐mediated anaerobic oxidative dehydrogenation cascade reaction of homopropargylic amines was developed for the synthesis of 1, 2‐disubstituted pyrrole derivatives (see figure).